2016
DOI: 10.1002/anie.201603639
|View full text |Cite
|
Sign up to set email alerts
|

Light‐Driven Transport of a Liquid Marble with and against Surface Flows

Abstract: Liquid marbles, that is, liquid drops coated by a hydrophobic powder, do not wet any solid or liquid substrate, making their transport and manipulation both highly desirable and challenging. Herein, we describe the light-driven transport of floating liquid marbles and emphasize a surprising motion behavior. Liquid marbles are deposited on a water solution containing photosensitive surfactants. Irradiation of the solution generates photoreversible Marangoni flows that transport the liquid marbles toward UV ligh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
122
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 144 publications
(129 citation statements)
references
References 34 publications
2
122
0
1
Order By: Relevance
“…[21] The lifetime is related to many aspects, like particles size, surface chemistry, and the external conditions. [21][22][23] The manipulation of single LMs, by the mechanical force, [24,25] magnetic locomotion [26][27][28] and light-driven motivation [29,30] have been developed in the past decade. Benefiting from the single LM manipulation and liquid control, the coalescence of the well-prepared LMs can mix the Coalescence and splitting of liquid marbles (LMs) are critical for the mixture of precise amount precursors and removal of the wastes in the microliter range.…”
mentioning
confidence: 99%
“…[21] The lifetime is related to many aspects, like particles size, surface chemistry, and the external conditions. [21][22][23] The manipulation of single LMs, by the mechanical force, [24,25] magnetic locomotion [26][27][28] and light-driven motivation [29,30] have been developed in the past decade. Benefiting from the single LM manipulation and liquid control, the coalescence of the well-prepared LMs can mix the Coalescence and splitting of liquid marbles (LMs) are critical for the mixture of precise amount precursors and removal of the wastes in the microliter range.…”
mentioning
confidence: 99%
“…We thus conclude that the colloidal structure was not controlled by the relative composition of cis/trans AzoTAB isomers in the bulk, instead we propose that it was mediated by the adsorption/desorption dynamics of AzoTAB.Upon UV-induced trans-to-cis isomerization, AzoTAB became more polar [35,36] and desorbed from the air/water interface in an analogous way to what was reported for similar photosensitive surfactants. [29] This lightinduced desorption of surfactants could induce aM arangoni stress toward the irradiated area, [31,33,[37][38][39] increasing particle confinement and promoting their crystallization. When irradiation smaller than the particle patch was used, some particle motion towards the irradiated area was observed and crystallization occurred on al arger area than the spot size ( Figure S6), confirming that Marangoni-induced confinement could contribute to particle crystallization.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…We recently showed that micromolar amounts of conventional cationic surfactants (for example,dodecyltrimethylammonium bromide,DTAB) induced the adsorption of anionic particles by decreasing the adsorption barrier at the air/water interface. [30] At such low surfactant concentrations (% CMC/ 1000-CMC/100, where CMC is the critical micelle concentration), the particles adsorbed with al ow contact angle ( % 308 8)a nd remained highly charged, forming disordered assemblies or polycrystalline patches in ap article-and surfactant-concentration-dependent manner.H ere,t o explore the possibility to dynamically switch particle assemblies at the air/water interface at constant composition, we used anionic polystyrene particles (diameter 5.1 mm) at af ixed concentration (0.01 mg mL À1 )a nd 10 mm of the AzoTAB photosensitive surfactant [31][32][33] (Figure 1A). AzoTAB is ac ationic surfactant with an azobenzene moiety in its hydrophobic tail, which can isomerize from trans to cis upon suitable light irradiation ( Figure 1B).…”
mentioning
confidence: 99%
“…Kavokine et al achieved liquid marble (LM) transport on a photoresponsive water solution surface driven by light (Figure 4b). [60] They investigated the influence of the liquid thickness on LM transport under light illumination in detail. The results indicated that the transport direction depends on the liquid thickness.…”
Section: Photoresponsive Liquid Mediamentioning
confidence: 99%
“…Reproduced with permission. [60] Copyright 2016, Wiley-VCH. c) Photodriven LM motion for material delivery owing to a surface-tension gradient generated by a temperature difference.…”
Section: Magnetoresponsive Solid Substratesmentioning
confidence: 99%